ANALISIS KESIAPAN MAHASISWA STRATA-1 UNIVERSITAS RIAU DALAM MENYIKAPI PERMENDIKBUD NO. 49 TAHUN 2014 TENTANG STANDAR NASIONAL PENDIDIKAN TINGGI - Hendriani, Susi; Ningsih, Dewita Suryati; Fitri, Kurniawaty (Jurnal Tepak Manajemen Bisnis, 2016)
This research aims to determine student readiness Strata-1 Universitas Riau in response toPermendikbud No. 49 year 2014 on National Standards Higher Education by collecting informationthrough questionnaires distributed to 300 students from three faculties: FKIP, Faculty of Fisheries, andthe Faculty of Economics.The results showed that the majority (59%) already know the information about Permendikbud No. 49year 2014 but 60% of students who already know the rules, there is only 30% understood what thePermendikbud enactment. 44% of participants stated that the current curriculum support for thecompletion of the study within five years. Related facilities support the learning process, studentsadmitted only 27% of participants who claim to support. For policies issued by each faculty has beengood according to participants. 48% of participants stated that the already available standard operatingprocedures (SOP) that support the completion of the study within five years, while only 23% ofparticipants stating have been implemented. Supporting of information systems that available is stillconsidered to be less while the facultys commitment to help students rated by the participants arerelatively well linked to the lecture, score, and preceptor. Similiarly with associated with non-academicservice by employees still need to be improved.